Konsep dan Implementasi Pendidikan Keagamaan Nonformal: Analisis Terhadap Pasal 52 RUU Sisdiknas Vesri Agustus 2022 - Jumaah, Jumaah; Mukhlis, Mukhlis; Jamaluddin, Jamaluddin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
The purpose of this research is to analyze the concept and implementation of non-formal religious education, with a focus on Article 52 in the Draft Law on the National Education System as of August 2022. The research method employs document text analysis by reading and critically evaluating the provisions of Article 52 in the Draft National Education System Law. Data for this study were collected through documentary research, gathering various documents related to the Draft National Education System Law as of August 2022. Data analysis was conducted by comparing and contrasting the content of Article 52 with the objectives of existing non-formal religious education and within the context of national education. The results of this analysis provide a comprehensive understanding of the concept and potential implementation of non-formal religious education within the proposed legal framework. The findings also illustrate potential implications in the context of national education. This research is expected to contribute to a better understanding of the development of non-formal religious education in the Draft National Education System Law as of August 2022 and provide important insights into changes in religious education in Indonesia.